Algas perifíticas: uma abordagem taxonômica e funcional em riachos inseridos em paisagens modificadas de cerrado - Oliveira, Pedro Henrique Francisco de (2021)
Considering the hierarchical conformation and connectivity present in dendritic drainages, the hydrological structuring of these systems may favor approaches to studies associated with patterns in aquatic metacommunities. Thus, investigating patterns in metacommunities using aquatic microorganisms as a study tool may favor approaches to studies associated with patterns of dispersion or species limitation, such as mass effects and species sorting. In addition, it is understandable to think that different functional traits present in species that make up these metacommunities may be modulated by environmental components (fundamental niche/realized niche) or spatial factors within an environmental gradient. In the present study, the first chapter “Effect of local, regional (land use) and spatial (organism dispersion) environmental variables on the structure of the periphytic algal community in Cerrado streams”, we seek to assess the relative importance of local environmental components (limnological), regional (land use) and spatial (dispersion capacity) variables for the periphytic community in Cerrado streams along the Piracanjuba River sub-basin. For the second chapter “Functional composition of periphytic algae in Cerrado streams inserted in modified landscapes”, we investigated how the functional traits present in species that make up the periphytic community respond to the variation of the regional (landscape) and local environmental component limnological variables) in streams inserted in modified Cerrado landscapes. We found 127 species, with a predominance of the Bacillariophyceae class in all streams and the average of remaining vegetation for the extension of the Piracanjuba River sub-basin was 40%. The periphytic community showed greater species replacement along the hydrographic network and relative importance only of the spatial component, since the functional attributes observed for this community were different along two gradients, nutrient availability, and percentage of natural remaining vegetation, respectively.